Caspofungin for primary antifungal prophylaxis after T‐cell–replete haploidentical stem cell transplantation with post‐transplant cyclophosphamide. (13th February 2019) - Mariotti, Jacopo; De Philippis, Chiara; Bramanti, Stefania; Sarina, Barbara; Tordato, Federica; Pocaterra, Daria; Casari, Erminia; Carlo‐Stella, Carmelo; Santoro, Armando; Castagna, Luca
Abstract: Objectives: T‐cell– replete haploidentical stem cell transplantation (Haplo‐SCT) with post‐transplant cyclophosphamide (PT‐Cy) is at high risk of invasive fungal infections (IFI), and anti‐mold–active drug is required for primary antifungal prophylaxis (PAP) according to international guidelines. No data are available on the efficacy of caspofungin as PAP in this setting. Methods: Here, we report our retrospective experience with 103 consecutive patients treated with caspofungin as PAP after Haplo‐SCT. Caspofungin was administered only during the pre‐engraftment phase. Results: Hundred‐day cumulative incidence of proven‐probable IFI (PP‐IFI) was 8.7% and median day of onset was 19 post‐SCT. No patient died of PP‐IFI, and overall survival (OS) and non‐relapse mortality (NRM) hazard ratio (HR) for patients experiencing IFI were 1.02 ( P = 0.9) and 0.7 ( P = 0.7), respectively. Three‐year overall survival (OS) and 1‐year non‐relapse mortality (NRM) were 55% and 19%, respectively. By univariate analysis, duration of neutropenic phase and partial remission pre‐transplant disease status were associated with increased incidence of IFI, but were not confirmed by multivariate analysis. Conclusion: In summary, PAP with caspofungin is an effective strategy for preventing IFI in the context of Haplo‐SCT with PT‐Cy. Further efforts are required in order to identify more potent strategies able to avoid the occurrence of breakthrough infections.